THE LEVEL OF HOPE-BASED THINKING AMONG UNIVERSITY STUDENTS - Souad Merghem; Hassina Yousfi; Malika Benchedda (International Journal of Innovative Technologies in Social Science, 2025)
This study aimed to measure the level of hope-based thinking among university students and examine differences according to gender (male/female) and field of study (scientific/humanities). The sample consisted of 140 students selected through convenience sampling. A descriptive research design was adopted, and Snyder et al.’s (1991) Hope Scale was employed for data collection. Data were analyzed using SPSS version 20, with the following findings:- University students demonstrated a high level of hope-based thinking.- No statistically significant differences were found according to gender.- No statistically significant differences were found according to field of study.